2003
DOI: 10.1590/s0036-36342003000900013
|View full text |Cite
|
Sign up to set email alerts
|

Improving cervical cancer screening in Mexico: results from the Morelos HPV Study

Abstract: Morelos es evaluar el uso de la prueba del virus de papiloma humano (VPH), en relación con la prueba de Papanicolaou, para el tamizaje de cáncer cervical. Material y métodos. El Estudio de VPH en Morelos actualmente se está llevando a cabo en México, para examinar la posibilidad de usar la prueba de VPH para la detección de cáncer cervical. Se evaluó el uso de la prueba de VPH en muestras auto-tomadas vaginales y en muestras cervicales tomadas por un clínico. Se comparó la aceptabilidad del uso de la prueba de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 59 publications
4
21
0
7
Order By: Relevance
“…16 Our findings suggest that women who do not participate in cervical cancer screening programs may be willing to provide a self-collected specimen. 17 Future studies should include an examination of the rate of follow-up testing among women found to be positive for high-risk HPV. In addition, improved methods are necessary to enhance uptake of follow-up interventions.…”
Section: Discussionmentioning
confidence: 99%
“…16 Our findings suggest that women who do not participate in cervical cancer screening programs may be willing to provide a self-collected specimen. 17 Future studies should include an examination of the rate of follow-up testing among women found to be positive for high-risk HPV. In addition, improved methods are necessary to enhance uptake of follow-up interventions.…”
Section: Discussionmentioning
confidence: 99%
“…There is no statistically significant difference in the sensitivity between cytology and either of the two HPV tests. The specificity of cytology is significantly higher than the specificity of the self HPV test (14% higher, 95% CI of [12][13][14][15][16][17] and clinician HPV test (12%, 95% CI of [9][10][11][12][13][14]. The NPVs of cytology and the HPV tests are similar, but the PPV of cytology is higher than the PPV for the HPV tests and the CIs do not overlap.…”
Section: Test Accuracy For Diagnosis Of High-grade Diseasementioning
confidence: 99%
“…11 Indeed, findings from the Morelos HPV Study, for example, indicate greater sensitivity for HPV testing compared with Pap testing for detecting cervical intraepithelial neoplasia (CIN) 2/3. 12 One limitation to this study is the fact that we do not know the characteristics of providers who did not respond to the survey, nor their reasons for not participating. In addition, these findings may not be generalizeable to public providers outside of the SSDF system in Mexico City.…”
Section: Discussionmentioning
confidence: 99%